Copper foil etching solution as well as preparation method, use method and application thereof

Through the compatibility of copper sulfate pentahydrate, ammonium ion-containing substances and ammonium fluoride, the shortcomings of existing copper foil etching liquid in terms of etching speed, uniformity and environmental protection performance are solved, and efficient, uniform and environmentally friendly copper foil is achieved. Etching effect.

CN119433540APending Publication Date: 2025-02-14SHENZHEN QINGYAN ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411620476.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing copper foil etching liquid has shortcomings in etching speed, uniformity and environmental protection performance, and it is difficult to meet the electronics industry's demand for high efficiency, uniformity and environmental protection.

Method used

The combination of copper sulfate pentahydrate, ammonium ion-containing substances (such as ammonia water or ammonium bicarbonate) and ammonium fluoride is used to significantly accelerate the etching rate through synergistic effects, improve etching uniformity, and improve etching quality and environmental protection performance.

Benefits of technology

It has achieved significantly accelerated etching rate, improved etching uniformity and improved etching quality, while reducing environmental pollution, which is in line with the trend of green production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The invention discloses a copper foil etching solution as well as a preparation method, a use method and application thereof. According to the copper foil etching solution, in every 1L of water, the addition amount of copper sulfate pentahydrate is 100g to 200g, the addition amount of a substance containing ammonium ions is 200ml to 500ml, and the addition amount of ammonium fluoride is 50g to 80g. The copper foil etching solution provided by the invention has high etching rate and high etching quality, has wide application prospects in the electronic material processing fields of printed circuit board manufacturing, electronic component production and the like, and can effectively meet the requirements of the industry on an efficient and environment-friendly etching process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of etching liquid, and in particular to a copper foil etching liquid, a preparation method, a use method and an application thereof. Background Art

[0002] In the context of the rapid development of the electronics industry today, copper foil is a key basic material in the manufacture of electronic components. The quality of its etching process directly affects the performance and production efficiency of electronic products. With the continuous advancement of technology, the requirements for the speed, uniformity and environmental protection of copper foil etching are getting higher and higher.

[0003] At present, there are many methods and etching solutions for etching copper foil. Traditional etching solutions such as ferric chloride system have low cost, but the etching speed is slow, the etching uniformity is not high, and a large amount of iron-containing sludge is produced, which is difficult to deal with later. The etching solution of persulfate system has high cost, poor solution stability, and great pollution to the environment.

[0004] In recent years, some new etching liquid formulas have emerged, but there are still many problems. For example, the etching rate of some etching liquids is unstable, making it difficult to ensure the consistency of product quality; some etching liquids increase the etching speed but cause uneven etching, affecting product performance; and some etching liquids, although they have solved the etching quality problem to a certain extent, have complex ingredients and high costs, which are not conducive to large-scale industrial production.

[0005] At the same time, with the increasingly stringent environmental regulations, the environmental pressure brought by the harmful substances contained in traditional etching solutions has become increasingly prominent. Therefore, the development of a new copper foil etching solution that can significantly accelerate the etching rate, ensure the uniformity of etching quality, and have good environmental performance has become an important issue that needs to be solved in the current electronics industry. Summary of the invention

[0006] In view of this, the present application provides a copper foil etching solution, a preparation method, a use method and an application thereof which can solve the above-mentioned problems.

[0007] The first aspect of the present application provides a copper foil etching solution, wherein per 1L of water, the addition amount of copper sulfate pentahydrate is 100g~200g, the addition amount of the substance containing ammonium ions is 200ml~500ml, and the addition amount of ammonium fluoride is 50g~80g.

[0008] In some embodiments, the substance containing ammonium ions includes at least one of ammonia water or ammonium bicarbonate. In the present application, the concentration of ammonia water is 25 wt %, and the concentration of ammonium bicarbonate is 27 wt %.

[0009] The second aspect of the present application provides a method for preparing the above copper foil etching solution, comprising the following steps: Providing a copper sulfate solution, and adding a substance containing ammonium ions to the copper sulfate solution to obtain a first mixed solution; Ammonium fluoride is added to the first mixed solution to obtain the copper foil etching solution.

[0010] The third aspect of the present application provides a method for using the above copper foil etching solution, comprising the following steps: Providing a copper foil to be etched, and placing the copper foil in an etching tank containing the copper foil etching solution; The temperature of the etching tank is controlled, and the copper foil etching solution is kept in a stirring state to perform etching.

[0011] In some embodiments, the temperature of the etching tank ranges from 25°C to 50°C.

[0012] In some embodiments, the stirring rate is 200 rpm to 500 rpm.

[0013] In some embodiments, after the etching step is completed, the process further includes washing the surface of the copper foil.

[0014] In some embodiments, after the step of “rinsing the surface of the copper foil”, the step further includes drying the copper foil.

[0015] A fourth aspect of the present application provides application of the above copper foil etching solution in the processing of electronic component materials.

[0016] In some embodiments, the electronic component material includes a copper clad laminate.

[0017] Compared with the prior art, the beneficial effects of the present application are at least: (1) Through a unique formula design, the ammonium ion-containing substance works synergistically with ammonium fluoride to significantly accelerate the etching rate, improve the etching uniformity, and enhance the etching quality.

[0018] (2) The copper foil etching solution provided in the present application has simple and stable components and high solution stability.

[0019] (3) Environmentally friendly ingredients reduce environmental pollution and comply with the trend of green production. DETAILED DESCRIPTION

[0020] The following examples are described in detail. The following examples are illustrative and are only used to explain the present application, and should not be construed as limiting the present application. The reagents and materials described in the following examples can all be obtained from commercial sources.

[0021] The present application provides a copper foil etching solution, wherein per 1L of water, the addition amount of copper sulfate pentahydrate is 100 g to 200 g, the addition amount of a substance containing ammonium ions is 200 ml to 500 ml, and the addition amount of ammonium fluoride is 50 g to 80 g.

[0022] In this application, copper sulfate pentahydrate is used as the main source of copper ions, participating in the etching reaction to oxidize the copper on the surface of the copper foil into copper ions. Substances containing ammonium ions can form stable copper ammine complex ions [Cu(NH3)4] with copper ions. 2+ , improve the solubility of copper in the etching solution, speed up the etching rate, and adjust the pH of the solution. The fluoride ions of ammonium fluoride can activate the surface of the copper foil and promote ion transfer. Ammonium fluoride and substances containing ammonium ions work together to improve etching efficiency; ammonium fluoride reacts with the tiny oxide layer or impurities on the surface of the copper foil, increases the surface area of ​​the copper foil exposed to the etching solution, promotes the etching reaction, and inhibits side reactions that may cause uneven etching or precipitation, thereby improving the stability of the etching solution and the etching quality. Ammonium ions play an auxiliary role in the etching process, maintaining the ionic strength and pH balance of the solution. Ammonium fluoride and substances containing ammonium ions work together to improve etching uniformity, inhibit side reactions, and ensure that the surface of the copper foil after etching is smooth and flat with good appearance.

[0023] In some embodiments, the substance containing ammonium ions includes at least one of ammonia water or ammonium bicarbonate. Ammonia water or ammonium bicarbonate can not only provide ammonium ions, but also provide an alkaline environment, which is further conducive to improving the etching rate.

[0024] The present application provides a method for preparing the above copper foil etching solution, comprising the following steps: Providing a copper sulfate solution, and adding a substance containing ammonium ions to the copper sulfate solution to obtain a first mixed solution; Ammonium fluoride is added to the first mixed solution to obtain the copper foil etching solution.

[0025] The present application provides a method for using the above copper foil etching solution, comprising the following steps: Providing a copper foil to be etched, and placing the copper foil in an etching tank containing the copper foil etching solution; The temperature of the etching tank is controlled, and the copper foil etching solution is kept in a stirring state to perform etching.

[0026] In some embodiments, the temperature range of the etching tank is 25°C to 50°C, for example, the temperature range of the etching tank is 25°C, 28°C, 30°C, 33°C, 35°C, 38°C, 40°C, 43°C, 45°C, 48°C, 50°C or in a range consisting of any two of the above values. Appropriate etching temperature is conducive to improving the etching rate and can prevent a large amount of volatilization of ammonia water.

[0027] In some embodiments, the stirring speed is 200 rpm to 500 rpm. For example, the stirring speed is 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm or in the range of any two of the above values. A suitable stirring speed can promote the uniformity of etching and the improvement of etching rate.

[0028] In some embodiments, after the etching step is completed, the process further includes washing the surface of the copper foil.

[0029] In some embodiments, after the step of “rinsing the surface of the copper foil”, the step further includes drying the copper foil.

[0030] The present application also provides the use of the above copper foil etching solution in the processing of electronic component materials.

[0031] In some embodiments, the electronic component material includes a copper clad laminate. In the present application, no special restrictions are imposed on the size and other conditions of the copper clad laminate.

[0032] The technical solution of the present application is further explained below in conjunction with specific implementation methods.

[0033] Example 1 In every 1L of deionized water, 120g of copper sulfate pentahydrate, 250ml of a substance containing ammonium ions and 60g of ammonium fluoride are added to prepare the raw materials required for preparing the copper foil etching solution, wherein the substance containing ammonium ions is ammonia water.

[0034] Pour deionized water into a clean container, slowly add copper sulfate pentahydrate crystals according to the above amount while stirring, until the copper sulfate pentahydrate crystals are completely dissolved, to obtain a copper sulfate solution. Slowly drop ammonia water into the copper sulfate solution, continue stirring, mix the solution evenly, to obtain a first mixed solution; then add ammonium fluoride powder to the first mixed solution, keep stirring until it is completely dissolved, to obtain a copper foil etching solution.

[0035] The temperature of the etching tank was set to 40°C, 2L of the copper foil etching solution was injected, a copper clad laminate with a length, width and thickness of 20cm×25cm×0.5cm was completely immersed in the copper foil etching solution, the copper foil etching solution was stirred at a rate of 300rpm, and the etching time was 15min.

[0036] After etching is completed, take it out quickly and rinse the copper clad laminate with a large amount of deionized water to remove the etching solution remaining on the surface, and then dry the etched copper clad laminate.

[0037] Example 2 In every 1L of deionized water, 100g of copper sulfate pentahydrate, 200ml of a substance containing ammonium ions and 70g of ammonium fluoride are added to prepare the raw materials required for the copper foil etching solution, wherein the substance containing ammonium ions is ammonia water.

[0038] Pour deionized water into a clean container, slowly add copper sulfate pentahydrate crystals according to the above amount while stirring, until the copper sulfate pentahydrate crystals are completely dissolved, to obtain a copper sulfate solution. Slowly drop ammonia water into the copper sulfate solution, continue stirring, and mix the solution evenly to obtain a first mixed solution; then add ammonium fluoride powder to the first mixed solution, keep stirring until it is completely dissolved, to obtain a copper foil etching solution.

[0039] The temperature of the etching tank was set at 35°C, 2L of the copper foil etching solution was injected, a copper clad laminate with a length, width and thickness of 20cm×25cm×0.5mm was completely immersed in the copper foil etching solution, the copper foil etching solution was stirred at a rate of 400rpm, and the etching time was 15min.

[0040] After etching is completed, take it out quickly and rinse the copper clad laminate with a large amount of deionized water to remove the etching solution remaining on the surface, and then dry the etched copper clad laminate.

[0041] Example 3 In every 1L of deionized water, 120g of copper sulfate pentahydrate, 250ml of a substance containing ammonium ions and 60g of ammonium fluoride are added to prepare the raw materials required for preparing the copper foil etching solution, wherein the substance containing ammonium ions is ammonia water.

[0042] Pour deionized water into a clean container, slowly add copper sulfate pentahydrate crystals according to the above amount while stirring, until the copper sulfate pentahydrate crystals are completely dissolved, to obtain a copper sulfate solution. Slowly drop ammonia water into the copper sulfate solution, continue stirring, and mix the solution evenly to obtain a first mixed solution; then add ammonium fluoride powder to the first mixed solution, keep stirring until it is completely dissolved, to obtain a copper foil etching solution.

[0043] The temperature of the etching tank was set to 40°C, 2L of the copper foil etching solution was injected, a copper clad laminate with a length, width and thickness of 20cm×25cm×0.5mm was completely immersed in the copper foil etching solution, the copper foil etching solution was stirred at a rate of 150rpm, and the etching time was 15min.

[0044] After etching is completed, take it out quickly and rinse the copper clad laminate with a large amount of deionized water to remove the etching solution remaining on the surface, and then dry the etched copper clad laminate.

[0045] Example 4 In every 1L of deionized water, 120g of copper sulfate pentahydrate, 250ml of a substance containing ammonium ions and 60g of ammonium fluoride are added to prepare the raw materials required for preparing the copper foil etching solution, wherein the substance containing ammonium ions is ammonia water.

[0046] Pour deionized water into a clean container, slowly add copper sulfate pentahydrate crystals according to the above amount while stirring, until the copper sulfate pentahydrate crystals are completely dissolved, to obtain a copper sulfate solution. Slowly drop ammonia water into the copper sulfate solution, continue stirring, mix the solution evenly, to obtain a first mixed solution; then add ammonium fluoride powder to the first mixed solution, keep stirring until it is completely dissolved, to obtain a copper foil etching solution.

[0047] The temperature of the etching tank was set to 40°C, 2L of the copper foil etching solution was injected, a copper clad laminate with a length, width and thickness of 20cm×25cm×0.5mm was completely immersed in the copper foil etching solution, the copper foil etching solution was stirred at a rate of 550rpm, and the etching time was 15min.

[0048] After etching is completed, take it out quickly and rinse the copper clad laminate with a large amount of deionized water to remove the etching solution remaining on the surface, and then dry the etched copper clad laminate.

[0049] Example 5 In every 1L of deionized water, 120g of copper sulfate pentahydrate, 250ml of a substance containing ammonium ions and 60g of ammonium fluoride are added to prepare the raw materials required for preparing the copper foil etching solution, wherein the substance containing ammonium ions is ammonia water.

[0050] Pour deionized water into a clean container, slowly add copper sulfate pentahydrate crystals according to the above amount while stirring, until the copper sulfate pentahydrate crystals are completely dissolved, to obtain a copper sulfate solution. Slowly drop ammonia water into the copper sulfate solution, continue stirring, mix the solution evenly, to obtain a first mixed solution; then add ammonium fluoride powder to the first mixed solution, keep stirring until it is completely dissolved, to obtain a copper foil etching solution.

[0051] The temperature of the etching tank was set at 20°C, 2L of the copper foil etching solution was injected, and a copper clad laminate with a length, width and thickness of 20cm×25cm×0.5mm was completely immersed in the copper foil etching solution. The copper foil etching solution was stirred at a rate of 300rpm, and the etching time was 15min.

[0052] After etching is completed, take it out quickly and rinse the copper clad laminate with a large amount of deionized water to remove the etching solution remaining on the surface, and then dry the etched copper clad laminate.

[0053] Example 6 In every 1L of deionized water, 120g of copper sulfate pentahydrate, 250ml of a substance containing ammonium ions and 60g of ammonium fluoride are added to prepare the raw materials required for preparing the copper foil etching solution, wherein the substance containing ammonium ions is ammonia water.

[0054] Pour deionized water into a clean container, slowly add copper sulfate pentahydrate crystals according to the above amount while stirring, until the copper sulfate pentahydrate crystals are completely dissolved, to obtain a copper sulfate solution. Slowly drop ammonia water into the copper sulfate solution, continue stirring, and mix the solution evenly to obtain a first mixed solution; then add ammonium fluoride powder to the first mixed solution, keep stirring until it is completely dissolved, to obtain a copper foil etching solution.

[0055] The temperature of the etching tank was set to 55°C, 2L of the copper foil etching solution was injected, a copper clad laminate with a length, width and thickness of 20cm×25cm×0.5mm was completely immersed in the copper foil etching solution, the copper foil etching solution was stirred at a rate of 300rpm, and the etching time was 15min.

[0056] After etching is completed, take it out quickly and rinse the copper clad laminate with a large amount of deionized water to remove the etching solution remaining on the surface, and then dry the etched copper clad laminate.

[0057] Comparative Example 1 A copper foil etching solution contains 400 grams of ferric chloride and 50 milliliters of hydrochloric acid in every 1 liter of deionized water, wherein the concentration of the hydrochloric acid is 37 wt %.

[0058] Pour deionized water into a clean container, slowly add ferric chloride powder according to the mass ratio while stirring, until the ferric chloride powder is completely dissolved to obtain a ferric chloride solution. Slowly drop hydrochloric acid into the ferric chloride solution, continue stirring, mix the solution evenly, and obtain a copper foil etching solution.

[0059] The temperature of the etching tank was set to 40°C, 2L of the copper foil etching solution was injected, a copper clad laminate with a length, width and thickness of 20cm×25cm×0.5mm was completely immersed in the copper foil etching solution, the copper foil etching solution was stirred at a rate of 300rpm, and the etching time was 15min.

[0060] After etching is completed, take it out quickly and rinse the copper clad laminate with a large amount of deionized water to remove the etching solution remaining on the surface, and then dry the etched copper clad laminate.

[0061] Comparative Example 2 A copper foil etching solution contains 250 grams of sodium persulfate and 50 milliliters of sulfuric acid in every 1 liter of deionized water, wherein the concentration of the sulfuric acid is 98 wt %.

[0062] Pour deionized water into a clean container, slowly add sodium persulfate powder according to the mass ratio while stirring, until the sodium persulfate powder is completely dissolved to obtain a sodium persulfate solution. Sulfuric acid is slowly added dropwise to the sodium persulfate solution, and the solution is continuously stirred to mix evenly to obtain a copper foil etching solution.

[0063] The temperature of the etching tank was set to 40°C, 2L of the copper foil etching solution was injected, a copper clad laminate with a length, width and thickness of 20cm×25cm×0.5mm was completely immersed in the copper foil etching solution, the copper foil etching solution was stirred at a rate of 300rpm, and the etching time was 15min.

[0064] After etching is completed, take it out quickly and rinse the copper clad laminate with a large amount of deionized water to remove the etching solution remaining on the surface, and then dry the etched copper clad laminate.

[0065] Comparative Example 3 In every 1L of deionized water, 120g of copper sulfate pentahydrate, 250ml of a substance containing ammonium ions and 60g of ammonium sulfide are added to prepare the raw materials required for preparing the copper foil etching solution, wherein the substance containing ammonium ions is ammonia water.

[0066] Pour deionized water into a clean container, slowly add copper sulfate pentahydrate crystals according to the mass ratio while stirring, until the copper sulfate pentahydrate crystals are completely dissolved to obtain a copper sulfate solution. Slowly drop ammonia water into the copper sulfate solution, continue stirring to mix the solution evenly, and obtain a first mixed solution; then add ammonium fluoride powder to the first mixed solution, keep stirring until it is completely dissolved, and obtain a copper foil etching solution.

[0067] The temperature of the etching tank was set to 40°C, 2L of the copper foil etching solution was injected, a copper clad laminate with a length, width and thickness of 20cm×25cm×0.5mm was completely immersed in the copper foil etching solution, the copper foil etching solution was stirred at a rate of 300rpm, and the etching time was 15min.

[0068] After etching is completed, take it out quickly and rinse the copper clad laminate with a large amount of deionized water to remove the etching solution remaining on the surface, and then dry the etched copper clad laminate.

[0069] <Performance Test> (1) Etching rate Etching rate V (μm / min) = (m1-m2) 10 6 / (ρ S T) Where m1 = weight of copper clad laminate before etching / g, m2 = weight of copper clad laminate after etching / g, ρ = density of etched copper foil on copper clad laminate / g / cm3 , S = area of ​​copper clad board / m 2 , T = etching time / min.

[0070] (2) Deviation value Where n is 5, n represents the five measurement points at the four corners and the center of the copper clad board; i is a natural number from 1 to 5, T i is the thickness at the i-th measurement position, T1 to T5 are the thicknesses at the four corners and the center of the sample, and σ refers to the thickness deviation of the copper clad laminate after etching with the etching solution. The deviation value can reflect the uniformity of etching.

[0071] (3) Appearance Observe whether the surface of the dried copper clad laminate is flat and smooth, whether there is precipitation and residue, whether the etched lines are clear, and whether there are obvious defects in the appearance, so as to evaluate the appearance grade, which is divided into excellent, good, and poor.

[0072] Excellent: The surface is flat and smooth, without obvious precipitation and residue, the etching lines are clear, and there are no obvious defects in appearance; Good: The surface flatness and / or smoothness is average, there is no obvious precipitation and residue, and there is no obvious flaw in the appearance; Poor: Poor surface flatness and / or smoothness, slight surface flaws, and / or precipitation or residue, and / or slightly blurred etching lines.

[0073] The dried copper-clad laminates in each embodiment and each comparative example were obtained, and etching rate test, etching uniformity test and appearance test were performed. The experimental data are shown in Table 1 and Table 2.

[0074] Table 1 Table 2 It can be seen from Table 1 and Table 2 that compared with Comparative Examples 1-3, the copper foil etching solution prepared by combining copper sulfate pentahydrate, a substance containing ammonium ions and ammonium fluoride in the present application has a higher etching rate, better etching uniformity and appearance, and can be applied to electronic material processing fields such as printed circuit board manufacturing and electronic component production, and can meet the high requirements for etching rate and etching uniformity.

[0075] The copper foil etching solution of Comparative Example 1 is composed of ferric chloride and hydrochloric acid, and the copper foil etching solution of Comparative Example 2 is a combination of sodium persulfate and sulfuric acid. After comparison, the etching rate, etching uniformity and appearance of Comparative Example 1 and Comparative Example 2 are both worse than those of Example 1. Comparative Example 3 replaces the ammonium fluoride in Example 1 with ammonium sulfide, and its etching rate, etching uniformity and appearance are also worse than those of Example 1.

[0076] Compared with Example 1, Examples 3-4 show that a suitable stirring rate can help to further improve the etching rate, etching uniformity and appearance of the copper foil etching solution.

[0077] Compared with Example 1, Examples 5-6 show that a suitable etching temperature can help to further improve the etching rate, etching uniformity and appearance of the copper foil etching solution.

[0078] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application is described in detail with reference to the above implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A copper foil etching solution, characterized in that: For every 1L of water, the amount of copper sulfate pentahydrate added is 100g~200g, the amount of ammonium ion-containing substance added is 200ml~500ml, and the amount of ammonium fluoride added is 50g~80g.

2. The copper foil etching solution according to claim 1, characterized in that The substance containing ammonium ions includes at least one of ammonia water or ammonium bicarbonate.

3. A method for preparing a copper foil etching solution according to any one of claims 1 to 2, characterized in that: The following steps are involved: Providing a copper sulfate solution, and adding a substance containing ammonium ions to the copper sulfate solution to obtain a first mixed solution; Ammonium fluoride is added to the first mixed solution to obtain the copper foil etching solution.

4. A method for using the copper foil etching solution according to any one of claims 1-2, characterized in that: The following steps are involved: Providing a copper foil to be etched, and placing the copper foil in an etching tank containing the copper foil etching solution; The temperature of the etching tank is controlled, and the copper foil etching solution is kept in a stirring state to perform etching.

5. The method for using the copper foil etching solution according to claim 4, characterized in that: The temperature range of the etching tank is 25°C to 50°C.

6. The method for using the copper foil etching solution according to claim 4, characterized in that: The stirring speed is 200 rpm to 500 rpm.

7. The method for using the copper foil etching solution according to claim 4, characterized in that: After the etching step is completed, the process further includes washing the surface of the copper foil.

8. The method for using the copper foil etching solution according to claim 7, characterized in that: After the step of "rinsing the surface of the copper foil", the copper foil is further dried.

9. Use of the copper foil etching solution according to any one of claims 1 to 2 in the processing of electronic component materials.

10. Use of the copper foil etching solution according to claim 9 in processing electronic components, characterized in that: The electronic component material includes a copper clad laminate.